2015
DOI: 10.3109/08037051.2015.1049466
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and cochlear hearing loss

Abstract: This paper presents a review of experimental and clinical research on the contribution of hypertension to cochlear hearing loss. Hypertension is one of the crucial risk factors underlying pathophysiological processes taking place in the cochlea. Several mechanisms explaining these processes have been described, mainly in animal models, such as the disturbance of the inner ear potassium recycling process due to the detrimental action of natriuretic hormone, and the decrease in the cochlear oxygen partial pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 59 publications
3
50
0
2
Order By: Relevance
“…That may be the reason why individuals with CC genotype of rs1485175 in GRM7 are less susceptible to noise than non-CC genotype. CNE [ 6 ], height [ 32 ], smoking [ 33 ], drinking [ 34 , 35 ], and hypertension [ 35 ], which are all hazardous factors for NIHL, were adjusted in the process of analyzing.…”
Section: Discussionmentioning
confidence: 99%
“…That may be the reason why individuals with CC genotype of rs1485175 in GRM7 are less susceptible to noise than non-CC genotype. CNE [ 6 ], height [ 32 ], smoking [ 33 ], drinking [ 34 , 35 ], and hypertension [ 35 ], which are all hazardous factors for NIHL, were adjusted in the process of analyzing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore hypertension and diabetes often co-exists in same individual. 16,17 The relationship between hypertension and T2DM is complex. Hypertension may exert impact upon the onset of T2DM through increasing vasoconstriction and vascular rarefaction, reducing skeletal muscle insulin sensitivity and detecting post receptor insulin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Tachibana et al [ 37 ] suggested that the primary target of hypertensive damage in the rat cochlea is the stria vascularis, which feeds the organ of Corti. Przewoźny et al [ 38 ] suggested that the subclinical damage to the stria vascularis includes the decrease in the cochlear oxygen partial pressure and disturbance of the ionic K + recycling. Borghi et al [ 34 ] suggested that the presence of tinnitus is the consequence of toxic damage of the labyrinth in most patients, which means that the onset of tinnitus might be an adverse event in patients treated with antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%